ANALISIS PELAKSANAAN PENJADWALAN PROYEK PEMBANGUNAN GEDUNG CLUBHOUSE DENGAN PENDEKATAN CPM DAN PERT PADA PT. XY - Kasid kasid; Muhammad Hermansyah (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2018)
The project scheduling establish the time sequence of various activities which has a certain time limit, this means that the project must be completed before or exactly at the specified time. The delay effect and result in delays to the completion of the overall project. The purpose of study is to analyze the scheduling of the project to find out how long a project can be completed, determine the critical path as well as optimize the time of execution of the project. Research methods used for the project implementation analysis of Clubhouse building construction using critical path method (CPM) and program evaluation and review technique (PERT). Results of the discussion and calculations obtained that the completion of the project still in accordance with the schedule that has been determained, with the critical path method (CPM) is 321 days, and the program evaluation and review technique (PERT), time most quickly resolved is 312 days (value of Z= 0,22%), the slowest time is 339 days (value of Z= 99,87%) and the most probable time is 325 days (value of Z= 49,20%). Be aware of the activities which constitute the critical path is the activities: A, B1, B2, B3, B4, C1, C2, C3, C4, C6, C5, C7, C8, D, and obtained the optimization of project completion time with the CPM method is 48 days, PERT method, time most quickly is 57 days,the slowest time is 30 days, and the most possible time is 44 days.